2013
DOI: 10.3109/09638288.2013.804594
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the National Service Framework for long-term (neurological) conditions: service user and service provider experiences

Abstract: Our research suggests that many service users with long-term neurological conditions experienced disconnections between services within their National Service Framework care pathway. For health and social care practitioners, a lack of continuity within a care pathway was suggested to be most pertinent following immediate care and moving to rehabilitative care. Our findings also indicate that service providers lack the necessary financial resources and staffing capacity to provide on-going and comprehensive reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Thirteen articles contributed evidence to this theory . Some HCPs felt pressure not to prioritise SMS because of worries about being seen to ‘pull their weight’ and fulfil organisational expectations (M), whereas for others it was felt impractical to integrate SMS into their role (M) because of a lack of time, a lack of continuity of care or fixed targets, all of which were caused by organisational structures (C) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen articles contributed evidence to this theory . Some HCPs felt pressure not to prioritise SMS because of worries about being seen to ‘pull their weight’ and fulfil organisational expectations (M), whereas for others it was felt impractical to integrate SMS into their role (M) because of a lack of time, a lack of continuity of care or fixed targets, all of which were caused by organisational structures (C) .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles contributed evidence to this theory. 7,8,29,37,39,44,51,52,57,60,[64][65][66] Some HCPs felt pressure not to prioritise SMS because of worries about being seen to 'pull their weight' and fulfil organisational expectations (M), 65 whereas for others it was felt impractical to integrate SMS into their role (M) because of a lack of time, a lack of continuity of care or fixed targets, all of which were caused by organisational structures (C). 37,57 HCPs working with PNCs perceived that providing funding for SMS was a low organisational priority because these conditions resulted in a relatively small proportion of acute hospital admissions compared with other conditions that were the focus of SMS efforts.…”
Section: Resultsmentioning
confidence: 99%
“…There have been attempts in the UK and Australia to integrate healthcare, human and community services for people with chronic conditions, as service fragmentation disrupts continuity of care, jeopardises patient access to services, and places additional stress on acute healthcare services (Bernard et al., ; Sixsmith et al., ). High‐risk patients are vulnerable to poorer health outcomes and costly unplanned readmissions for, without appropriate support in the peridischarge period, they have low capacity for self‐care (Leppin et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom (UK), NHS reforms towards integrated care and joined‐up interagency services, to simplify intermediaries, reflect concern for the adverse impact that the fragmentation of health and social services has on continuity of care. Integrated care within healthcare and across service boundaries is considered imperative to support people with long‐term neurological conditions (LTNCs), which are often progressive and fluctuating (Bernard, Aspinal, Gridley, & Parker, ; Sixsmith, Callender, Hobbs, Corr, & Huber, ). Integrated care is also a proposed mechanism for reducing ED presentations and unplanned hospital admissions (London Clinical Networks, ).…”
Section: Introductionmentioning
confidence: 99%
“…An example is a study that conducted semi-structured interviews with participants in the implementation of a National Service Framework for Long-Term Neurological Conditions in the United Kingdom. The study found that clients experience that effective care is provided while they are in the hospital setting, but that when they return to communities needs still exist, but services provided are inadequate [30].…”
Section: Meso Levelmentioning
confidence: 99%